Regular moderate exercise during pregnancy does not have an adverse effect on the neurodevelopment of the child. (4th February 2015) - Hellenes, Olav Mørkved; Vik, Torstein; Løhaugen, Gro C.; Salvesen, Kjell Åsmund; Stafne, Signe N.; Mørkved, Siv; Evensen, Kari Anne I.
Abstract Aim Current U.S. guidelines suggest that pregnant women should exercise regularly during pregnancy, and we examined the neurodevelopment of the children whose mothers had taken that advice. Methods This Norwegian study included 188 children whose mothers had followed a structured exercise protocol and 148 control children whose mothers had not. Their cognitive, language and motor skills were assessed at 18 months of age by the Bayley Scales of Infant Development‐III and daily life functioning with the Ages and Stages Questionnaire. Results No significant differences were found between the two groups. Subgroup analyses revealed that the children whose mothers had exercised had a slightly lower motor composite score (mean: 97.6, 95% CI: 96.0–99.2) than the control group (mean: 100.0, 95% CI: 98.6–101.5) (p = 0.03). Boys in the intervention group had lower fine motor scores (mean: 10.6, 95% CI: 10.3–11.0) than boys in the control group (mean: 11.5, 95% CI: 11.0–11.9) (p = 0.01). Conclusion Our main finding was that regular moderate exercise during pregnancy does not adversely affect neurodevelopment in children. The lower motor scores in the subgroup analyses are probably clinically insignificant, but the lower fine motor scores for boys in the intervention group warrant further research.